Latency measures of pattern-reversal VEP in adults and infants: different information from transient P1 response and steady-state phase. - Lee, J; Birtles, D; Wattam-Bell, J; Atkinson, J; Braddick, O (2012)
PURPOSE: Temporal properties such as the peak latency of pattern-reversal (PR) visual evoked potentials (VEPs) have been found to be a sensitive indicator of visual development. Latency can be assessed from the slope of a plot of phase against temporal frequency (TF) for steady state VEP measurements as well as from the transient P1 peak. This study aimed to discover whether the two methods provide different information regarding early visual development. METHODS: Developmental changes of the transient peak latency were tracked using low TFs of one to four reversals per second (r/s) and a spatial frequency (SF) of 0.24 cycles per degree (cpd) in comparison with latencies calculated from the phase versus TF gradient in the range of 1 to 19 r/s. PR-VEP responses were recorded from 81 adults and 137 infants (ages 3.6-79 weeks). RESULTS: Values of the calculated and transient peak latencies were similar in adults, but the calculated latency was statistically longer than transient peak latency in younger infants. Moreover, while the transient peak latency asymptoted to an adult value of 104 ms at approximately 15 weeks of age, the calculated latency did not asymptote until after 30 weeks. CONCLUSIONS: In this study, the effectiveness of the phase-based method to calculate latency was confirmed. In infants, the rapid decrease of P1 latency may be due to the progressive maturation of conduction time in the afferent visual pathways, with the development of adult levels of phase-based calculated latency being due to the maturation of later cortical processing in infants.